A teaching program based on the Authentic Instruction approach and its effectiveness in developing health awareness and future thinking skills among second-grade students in science - Kariri, Maryam Abdu; Al-Arini, Hanan AbdulRahman (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to build a teaching program based on the Authentic Instruction approach and its effectiveness in developing health awareness and future thinking skills among second-grade students in science. To achieve this goal, the study followed the experimental approach with its quasi-experimental design. The study was applied to a sample of (58) female students from the second intermediate grade. The study finds the following results: There is a statistically significant difference at the level (α ≤ 0.05) between the mean scores of the students of the experimental and control groups in the dimensional application of the health awareness scale in favor of the experimental group. And There is a statistically significant difference at the level (α ≤ 0.05) between the mean scores of the female students of the two experimental and control groups in the dimensional application of the future thinking skills test in favor of the experimental group. The study made several recommendations, the most important of which are: the use of the teaching program based on the realistic teaching approach in developing health awareness and future thinking skills; Due to its excitement and suspense in the educational process, which raises the students’ motivation towards learning, take advantage of the teaching model developed in this study, and use it in building teaching programs to teach different courses, holding training courses and workshops for science supervisors and teachers; To train them to employ the approach of realistic teaching in teaching science courses.